Pengaruh Komunikasi Pemasaran, Social Media Marketing dan Harga Terhadap Keputusan Pembelian - Kusumawardhani, Trisnawati (Cattleya Darmaya Fortuna, 2023)
This research was conducted with the aim of finding out the influence of marketing communications, social media marketing and prices on Tokopedia marketplace purchasing decisions. The method used is a quantitative research approach. The sample method is nonprobability sampling with purposive sampling. Samples were used that met the research criteria with a total of 100 respondents. The data collection method uses a questionnaire with likert scale. The data analysis technique used in this research is multiple linear regression. Data analysis using IBM SPSS Statistics 26. The results of the analysis show that partially the variables marketing communication, social media marketing and price have significant positive influence on purchasing decisions. The results of the simultaneous analysis show that the variables marketing communication, social media marketing and price have positive and significant influence on purchasing decisions.